Effect of fungal infections on nutritional value of papaya fruits - U. Gawai, S. G. Sawant and D. (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The nutritional value of fruits chiefly depends on the quality & quantity of nutritive substances. Various fungi causes rots in fruits of papaya. The fungi are very selective in their nutritional requirements. They influence the stored substances by observing them or by converting some of the complex forms into simple ones. In the present investigation total five fungi were isolated from papaya fruits. The effect of these fungi on considerable losses in proteins, ash and nitrogen content were observed in the papaya fruits. In general the amount of the amino acids in free as well as bound forms increased in infected fruits. Considerable decrease in total sugar and increase in reducing sugar was observed in most of the fungi.